(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Mammary tuberculosis is a rare entity in western countries but a continuing problem in endemic areas like Bangladesh. Its clinical patterns and treatment strategies are changing day by day. In this study we showed our clinical experience on 50 cases of mammary tuberculosis. This is a prospective nonrandomized observational descriptive study. A total of 50 consecutive adult female patients with no other co morbid diseases and who were diagnosed cytologically or histologically as case of mammary tuberculosis were enrolled in the study over a period of 04 years since 2006 to 2010 in general surgical unit of Chittagong Medical College Hospital and Chittagong general hospital. The average ages of presentation were 38 years. Ten(20%) patients were lactating at the time of presentation and six(12%) patients were nulliparious. 40(80%) patients had breast lump at presentation. Among them 20(40%) presented with multiple sinuses with lump,10(20%) had abscess with lump,05(10%) had abscess drainage scar with underlying lump and 05(10%) presented with isolated breast lump. 06(12%) presented with multiple sinuses with abscess formation. Another 04(8%) patients had multiple sinuses only at presentation. Ten (20%) had constitutional symptoms in the form of fever, weight loss and night sweat. Twenty (40%) had axillary lymphaedenopathy in association with breast lesion. Diagnosis were confirmed by cytological and or histological findings of epitheloid granulomas.All patients were given antitubercular chemotherapy ( 9 months regimen) in combination with surgical intervention (45 out of 50 cases) as necessary in the form of excision of masses, incision and drainage of abscess and sinectomy. Mammary tuberculosis is a continuing problem in developing countries. Presentation may mimic benign lesion or carcinoma of the breast. Diagnosis can be made on high index of suspicion in endemic areas. Cytological or histological findings of granulomatous inflammation consisting of caseation necrosis, epitheloid cell and Langhans giant cell can give definitive diagnosis. Treatment is by anti tubercular chemotherapy with or without surgical intervention where necessary. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21063